Analisis Kecenderungan, Faktor dan Dampak Agresi Verbal pada Anak dan Remaja - Syahira Hayu Ananta; Putri Rahmawati; Marsya Selia; Risma Anita Puriani; Rizki Novirson (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research is motivated by the increasing cases of verbal aggression among children and adolescents, which have a significant impact on their psychological well-being and social environment. The aim of this study is to analyze the tendencies, causal factors, and impacts of verbal aggression in children and adolescents, as well as to provide effective recommendations for its management. The method used is a literature review with a descriptive qualitative approach, examining various scientific journals related to verbal aggression, verbal abuse, and the influencing factors. The main findings show that verbal aggression often arises due to family factors, social environment, media, and socioeconomic pressures; this behavior not only increases the risk of depression, anxiety, and low self-esteem in victims but also has long-term negative effects on the perpetrators. The implications of this study emphasize the importance of early detection and the active roles of teachers, parents, and school counselors in preventing and managing verbal aggression through communication skills education, psychological interventions, and strengthening school policies to create a safe learning environment that supports the social-emotional development of children and adolescents.